Coordinated hospital-community organisation model for the prevention, monitoring and treatment of patients with addiction and HCV - Balestra, Roberta (Acta Biomedica Atenei Parmensis, 2018)
Background Hepatitis C Virus (HCV) infection is a common cause of chronic liver disease, cirrhosis and hepatocellular carcinoma. Epidemiological studies have shown a prevalence amongst the general Italian population that varies between 0.4% and 16.2%, depending on the age bracket and the geographic area considered. The prevalence amongst persons who inject drugs (PWID) is approximately 70%, making this population one of the main reservoirs of the virus. The complex issues of addiction impact access to antiviral therapy, despite the presence of efficacious treatments, with considerable personal, family and social costs. According to the available literature, testing is a critical issue in Drug Addiction Services and at the current time a mere 37.3% of users are screened, which translates into delayed diagnosis and access to antiviral therapies, with a considerable risk of an exacerbation of the clinical situation and of unconscious transmission of the condition to others. Purpose To describe the coordinated organisation model for the therapeutic management of patients who inject drugs with HCV, implemented by Trieste Department of Dependency (DoD); to monitor its clinical efficacy and its ability to guarantee continuing care between hospital and community medicine settings. Methods The aim of the model is to promote certain activities and partnerships that are already implemented by infectious disease/ hepatology specialists as part of the coordinated HCV prevention and treatment programme and to test novel strategies for preventing post-treatment reinfection. The programme is broken down into three different specialised levels: • the first level consists of on-site screening, performed at the Department of Dependency outpatient clinic; • the second level is characterised by clinical and diagnostic investigations conducted by the infectious diseases/hepatology specialist, to whom the subject is referred when found to be positive at level one; • the third level consists of pharmacological treatment and follow-up, which commences when the subject starts treatment with direct-acting antivirals; three different medicinal product management methods are contemplated, depending on the individual’s level of self-sufficiency. Follow-up starts at the end of treatment and lasts a year. Conclusions The experience of Trieste DoD demonstrates the feasibility of a coordinated management organisation model with hospital specialists and its efficacy in the clinical management of a population of PWID with viral hepatitis C. The provision by the DoD of daily, highly organised on-site screening managed by a specially- trained medical team has proven strategic for facilitating access to and compliance with the protocol for treatment with new direct-acting antivirals (DAA). In this team, a key role is played by the nurse, as the professional who manages the fiduciary relationship that is closest to the patient. A linkage to care approach that is differentiated according to the level of self-sufficiency and the complexity of the patient’s needs makes it possible to avoid drop-out and to complete all pharmacological programmes. Harm reduction activities are important for pursuing changes in at-risk behaviour and preventing reinfection and are implemented at different time points during treatment and follow-up.